2023
DOI: 10.1097/md.0000000000033917
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the pharmacological mechanism of Duhuo Jisheng Decoction in treating intervertebral disc degeneration based on network pharmacology

Abstract: Background: The purpose of this study was to examine the mechanism of Duhuo Jisheng Decoction (DHJSD) in the treatment of intervertebral disc degeneration (IVDD). Methods: The active compounds of DHJSD and their corresponding targets were obtained from the TCMSP database. “Intervertebral disc degeneration” was used as a search term in the DisGeNET, GeneCards, Comparative Toxicogenomics Database, and MalaCards database to obtain disease-related targets. Following the discovery of overlapping DHJSD and IVDD ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…As a complementary therapy, DHJSD is widely for the management of bone and joint diseases in China; however, its exact mechanism has not been completely elucidated. Existing studies have confirmed that DHJSD regulates inflammatory factors, reduces apoptosis and pyroptosis of nucleus pulposus cells, and inhibits extracellular matrix degradation [9][10][11][12], indicating the multiple mechanisms of action of DHJSD in osteoarthritis (OA).…”
Section: Methodsmentioning
confidence: 99%
“…As a complementary therapy, DHJSD is widely for the management of bone and joint diseases in China; however, its exact mechanism has not been completely elucidated. Existing studies have confirmed that DHJSD regulates inflammatory factors, reduces apoptosis and pyroptosis of nucleus pulposus cells, and inhibits extracellular matrix degradation [9][10][11][12], indicating the multiple mechanisms of action of DHJSD in osteoarthritis (OA).…”
Section: Methodsmentioning
confidence: 99%
“…[19] Many recent studies have partially established the usefulness of Chinese medicine in treating IDD, with the primary mechanisms including reduction of oxidative stress, regulation of inflammatory response, and decrease of myeloid cell death, among others. [20,21] AS IV is a natural saponin purified from the traditional Chinese medicine Astragalus membranaceus , which has anti-inflammatory, antioxidant, anti-apoptosis and anti-cancer pharmacological activities. [22] Previous studies have shown that AS IV inhibits IL-1β-induced chondrocyte inflammatory mediators, apoptosis and ECM degradation, and alleviates the progression of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%